Czytając Elegie Rainera Marii Rilkego - Surowska, Barbara (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article discusses the book Rycerz i śmierć written by Katarzyna Kuczyńska-Koschany. The book includes essays on Reiner Maria Rilke’s Duino Elegies published earlier that have been revised and updated. The poem cycle called the Duino Elegies is composed of ten separate poems written in 1912, 1913, 1915 and 1922, i.e. at the peak period of the poet’s imagination and mental activity. The reviewer provides a detailed analysis the first four chapters of the book in which three elegies written before the outbreak of the first war, and the fourth that originated when the war was raging on, are presented. The reviewer appreciates the author’s careful preparation for the book and the ambitious agenda of the author to describe in a synthetic form, for the first time in Poland, the whole cycle of Rilke’s elegies with their Polish translations along with their quality evaluation and comparison taken into consideration, as well as some presentations of German interpretations from prominent specialists in the life and the literary output of Rilke. However, the reviewer is not ready to buy all of the author’s claims and points at numerous, perhaps too numerous, errors, distortions in facts and erroneous reading of the original texts written in German, which, to a high degree, lowers the perceived quality of the discussed book.